Profil Kajian Administratif dan Ketepatan Resep Obat Antihipertensi di Puskesmas Darma Kabupaten Kuningan - Anugra Diputra, Angga; Febriliana, Gina (Jurnal Medika Farmaka, 2023)
Introduction: There are still many problems with prescription completeness, such as incomplete patient information. Hypertension is one of the most common cardiovascular diseases and the cases most often occur in the community. The high number of cases of hypertension or its complications causes the use of antihypertensive drugs to increase, and the chances of inappropriate drug selection in hypertensive patients are higher. The purpose of this study was to determine the percentage of completeness of prescriptions and the accuracy of drug selection in outpatient hypertension patients at the Darma Health Center for the period July - December 2020 when viewed based on the right drug and the right dose. Methods: The type of research carried out is non-experimental observational research. Data collection was carried out retrospectively through outpatient medical records of hypertension patients for the period July - December 2020. The sampling method used in this study was purposive sampling. Results: From a total of 570 prescriptions for hypertension patients, a sample of 85 patients was used. The results of the administrative review of prescriptions obtained 100% patient data completeness, 100% doctor's name, 100% doctor's initials, 100% prescription writing date and 100% prescription room/unit. The results of the evaluation of the accuracy of antihypertensive drug prescriptions showed that the accuracy of prescribing based on the correct criteria for the drug was 71,8% and based on the criteria for the correct dose of 100%. Conclusion: This study revealed that the administrative compliance and accuracy based on the right dose criterion of antihypertensive drug prescriptions were all in compliance, but there were still discrepancies for the right drug criterion.